Exploration of the adverse effects of shift work in a multicultural environment - Bures, Marek; Cadkova, Vera; Altunpinar, Ali (Work, 2019)
BACKGROUND: Given that shift work spreads across many different business sectors, studies of its adverse effects are very topical. Much research has been done on the negative impact of shift work, but many researchers have not focused on its impact in a multicultural environment. OBJECTIVE: The aim of this study was to map out how shift work is perceived by workers in two different shift regimes and two national groups. METHODS: The research was carried out on Czech manufacturing workers and Turkish airport ground personnel using a questionnaire. The impact of shift work was studied from physical, mental, social and health aspects with connection to family status and gender. For statistical evaluation, Pearson's chi-squared test of independence was used. The effect of shift work on workers' performance and scrap rate was analysed only on the sample of the manufacturing workers. RESULTS: Fifty-five Czech male workers, 49 Turkish male workers and 60 Turkish female workers participated in the survey. The dependence between sexes was confirmed for mental aspects and sleeping routines. The main difference between nationalities is in work attitude, social aspects and sleeping routines. According to the family status, the difference was confirmed in all areas except social aspects. The lowest values of productivity and the highest scrap rate were observed on night shifts and the maximum productivity and lowest scrap rates were observed on afternoon shifts. CONCLUSIONS: Some of the basic assumptions were confirmed which suggests that a multicultural environment has an influence on the perception of shift work by the nations and gende.
Keywords: Male; zpracovatelský průmysl; práce na směny; vliv směnného provozu na zdraví; Adult; Turkey; Česká republika; průzkumy a dotazníky; Shift Work Schedule; Sleep Disorders, Circadian Rhythm; Czech Republic; poruchy cirkadiánního rytmu (spánek); Cultural Diversity; pracoviště; Middle Aged; lidé středního věku; Adolescent; Turecko; Humans; Work Schedule Tolerance; Surveys and Questionnaires; dospělí; mužské pohlaví; mladiství; kulturní různorodost; Manufacturing Industry; Workplace; lidé